Jumping and Landing Kinematics in Spanish Female Soccer Players: A Comparison Between Elite and Non-Elite Athletes - Francisco Javier Robles-Palazón; Alba Aparicio-Sarmiento; María Teresa Martínez-Romero; Mark De Ste Croix; Francisco Ayala (Sensors)
Landing from a jump has been identified as a common situation of increased risk in sport and the tuck jump assessment (TJA) has been proposed for a comprehensive examination of landing mechanics. However, group-specific data on female athletes are limited. The purpose of this study was to examine the movement mechanics during a TJA in Spanish female soccer players and to explore potential differences between players of different performance levels. A total of 96 (elite and non-elite) female soccer players performed a TJA, and a rater visually graded the technique using the modified 10-item scoring system (0, 1, or 2 for “none”, “small”, or “large” flaws). Descriptive statistics were calculated. The association between the flaws and performance groups was assessed using the chi-square test. Almost 90% of all players involved were categorized with small and large flaws for the item “Lower extremity valgus at landing”. The proportion of players categorized with technical flaws was also high for “Foot contact timing not equal” (85%) and “Does not land in same footprint” (82%). Differences between elite and non-elite players were only found for “Foot placement not parallel” and “Excessive landing contact noise” (p < 0.008). These results reveal the importance of implementing training programs to reduce jumping and landing deficits in female soccer players, independently of the players’ level of performance.